Impact of previous surgery on sentinel lymph node mapping: Hybrid SPECT/CT before and after a unilateral diagnostic breast excision. (December 2016) - Zetterlund, Linda; Gabrielson, Stefan; Axelsson, Rimma; de Boniface, Jana; Frisell, Jan; Olsson, Annie; Celebioglu, Fuat
Abstract: Background: Earlier studies have shown conflicting results regarding the accuracy of sentinel lymph node biopsy after previous breast surgery, especially after a surgical biopsy. Purpose: To compare lymph drainage patterns before and after a diagnostic unilateral surgical biopsy using the exact anatomical localisation of sentinel lymph nodes defined by SPECT/CT. Material and methods: Thirty-seven women planned for unilateral surgical excision of an unsuspicious breast lesion were prospectively examined between September 2011 and January 2015. Hybrid SPECT/CT lymphoscintigraphy of the thorax and neck region with bilateral subareolar injections of 99m Tc-Nanocoll was performed one week before and six weeks after surgery. The non-operated side served as a control. The primary outcome measure was the concordance between pre- and postoperative number and localisation of sentinel lymph nodes. Results: Sentinel lymph node detection rate with SPECT/CT on operated sides was 91.9 per cent (34 of 37 procedures), to be compared with a detection rate of 93.7 per cent on all non-operated sides (104 of 111 procedures, P = 0.771). Partial or total concordance regarding the localisation and number of sentinel lymph nodes was 85.7 per cent (30 out of 35) on operated and 88.9 per cent (32 out of 36 patients) on non-operated breast sides (P = 0.735). Conclusion: Breast surgery slightly decreased the concordance between pre- and postoperative sentinel lymph nodes, but this finding was not statistically significant. Our results thus support that it is feasible to perform a sentinel lymph node biopsy after previous breast excisional surgery with an acceptable level of safety. Highlights: Sentinel lymph node mapping with hybrid SPECT/CT after prior excisional biopsy. The contralateral breast served as a control for reproducibility purposes. The detection rate was not significantly lower on operated sides. The concordance between scans was not significantly lower on operated sides. Our results support the feasibility with SLN biopsy after prior excisional biopsy.